2020
DOI: 10.1108/ijm-08-2019-0404
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership towards sustainability in higher education – an integrated green model

Abstract: PurposeSustainability in higher education has drawn the attention of various scholars. However, to date, very few studies have examined the human side of green employee behaviour towards sustainability. Thus, to address this gap, this study aims to analyse the effect of green authentic leadership towards sustainability in higher education, with the intervening impact of green internal branding and green training.Design/methodology/approachThe study examined the data collected from faculty and their immediate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 85 publications
0
44
0
4
Order By: Relevance
“…It is believed that employees’ enduring commitment and inclination to the values of organizational brand are necessary while seeking the shift toward sustainability. According to Srivastava et al [ 56 ], this transformation is challenging, complicated, durable, and burdensome. Although the main objective of universities might be to educate and perform administrative functions, teaching and research are less likely to highlight sustainability.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…It is believed that employees’ enduring commitment and inclination to the values of organizational brand are necessary while seeking the shift toward sustainability. According to Srivastava et al [ 56 ], this transformation is challenging, complicated, durable, and burdensome. Although the main objective of universities might be to educate and perform administrative functions, teaching and research are less likely to highlight sustainability.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…HRM is found to improve employee well-being and helping behaviors under ethical leadership when the perception of its practices is high ( Kalshoven and Boon, 2012 ). Research on green HRM has also shown that such practice can interact with VBL behaviors and affect the organization’s environmental performance ( Ren et al, 2020 ) and sustainability ( Srivastava et al, 2020 ) and improve citizenship behaviors for the environment at both team and individual levels ( Luu, 2019 ).…”
Section: The Role Of Organizational Human Resource Management Practicesmentioning
confidence: 99%
“…GHRM has been explored both in manufacturing (Bag and Gupta, 2019; Ndubisi, 2019) and service provision contexts (Fawehinmi et al , 2020), including, for example, health care services (Mousa and Othman, 2020), higher education provision (Srivastava, 2019; Yusoff et al , 2019) and hospitality/tourism management (Siyambalapitiya et al , 2018; Pham et al , 2019a, b, c; Kim et al , 2019). GHRM is influenced by a number of organizational factors and context and can be found in different levels of maturity in organizations (Nejati, 2019; Yuriev, 2019; Moktadir et al , 2019).…”
Section: How To Promote Ghrm In Organizations?mentioning
confidence: 99%
“…The article “Assessing the green behaviour of academics: The role of green human resource management and environmental knowledge” (Fawehinmi et al , 2020) addresses the role of GHRM in promoting green behaviour of academics, through assessment of green performance of scholars in an academic environment. In the same line of research, the manuscript “Authentic leadership towards sustainability in higher education- an integrated green model” (Srivastava, 2019) adds to the literature of GHRM that top management leadership plays a fundamental role in the process of greening the workforce. However, GHRM proved to be a relevant topic for other industrial sectors as well, such as the automotive sector, according to the article “Analysing green human resource management indicators of automotive service sector” (Luthra et al , 2019)…”
Section: Final Remarks and Research Agendamentioning
confidence: 99%
See 1 more Smart Citation